Abundance and Diversity of Echinoderms in Seagrass and Coral Reefs Ecosystems - Abdul Kadir Jailani; Femy M Sahami; Miftahul Khair Kadim (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the abundance and diversity of Echinoderms in seagrass and coral reef ecosystems in the waters of Tomini Gulf, Lamu Village, Batudaa Pantai, Gorontalo Regency. This research was conducted for 3 months, from July to September 2017. The method used was the quadrant transect method in seagrass ecosystems and in coral reef ecosystems using the Line Intercept Transect (LIT) method. Observations were made at 3 stations based on the presence of seagrasses and coral reefs. The results showed that the highest abundance in the seagrass ecosystem is Ophiolepis superba with a value of 36.48%, in the coral reef ecosystem was the type of Diadema sp with a value of 52.73%. The highest echinoderms diversity in seagrass ecosystem was obtained at Station 1 with a value of 0.7433 which was included in the medium category and the highest coral reef ecosystem at Station 3 with a value of 0.6624 and included in the medium category.